De-duplicating Encrypted Data using ABE & ECC for Secured Cloud Environment - Sri Sumanth, Ch.; Raja Rajeshwari Reddy, Y.; Sandeep Chaitanya, N. (International Journal of Engineering and Technology, 2018)
Attribute-Based Encryption (ABE) was widely used in cloud environments, where owner outsource data to cloud service with an encrypted format and share his data with other users with some specific credentials or attributes. In an existing ABE, Data secure deduplication was not involved only attribute based encryption was involved. In our paper, we have used a deduplication technique with a secured data attribute based encryption using ECC(Elliptic Curve Cryptography) in multi cloud setting. Where a duplicate detection is responsible by private cloud and storage space is managed by public cloud. Compared to other systems we have designed data confidentiality with settings of access policy avoiding the share of decryption keys. And also we have created a system that create only one cipher text as per access policy for a plaintext for different owners data with a different access policy and without revealing the plain text to users.